The Role of Social Media in Enhancing Public Participation in Government Policy-Making Processes - Sarianti Aruan; Timbul Dompak (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to comprehensively explore the role of social media as a strategic instrument in increasing public participation in the process of formulating and implementing government policies. In the era of digital transformation, social media has shifted from being a mere personal communication channel to a virtual public space that enables real-time two-way interaction between state authorities and citizens. Using a descriptive approach, this study analyzes how platforms such as X, Instagram, and Facebook function as bridges to capture public aspirations in a more inclusive and transparent manner. The results show that effective use of social media by government agencies can break down traditional bureaucratic barriers, allowing previously marginalized groups to provide input on draft regulations. Furthermore, the transparency of information offered through digital content can increase public trust, which is the main foundation of policy legitimacy. However, challenges such as the spread of disinformation and the phenomenon of digital polarization remain obstacles that need to be mitigated through strong digital literacy and accountable content moderation. This study concludes that social media is no longer merely a complementary tool but a core component of democratic governance (e-government). The research recommendations emphasize the importance of strengthening human resource capacity within government to manage crisis communications and collect feedback from digital citizens to create policies that are more responsive and relevant to future public needs.